Occurrence of blastocystis in patients with clostridioides difficile infection (2020)
Clostridiodes difficile comprises a public-health threat that has been understudied in Colombia. Hypervirulent strains of C. difficile harbor multiple toxins, can be easily spread, and can have their onset of disease within healthcare facilities (HCFO) and the community (CO). Studies have shown that a disrupted microbiota (e.g., dysbiosis) may allow C. difficile infection (CDI). It has been suggested that dysbiosis prevents colonization by the anaerobic eukaryote Blastocystis, possibly due to an increase in luminal oxygen tension. No study has found co-occurrence of CDI and Blastocystis. Therefore, we aimed to determine the frequencies of C. difficile and Blastocystis infection/colonization in 220 diarrheal fecal samples. Molecular detection by PCR for both microorganisms was performed, with descriptive analyses of four variables (CDI detection, determination of C. difficile toxigenic profiles, Blastocystis detection, and patient site of onset). We demonstrate a significant association between the presence of Blastocystis and CDI, with coinfection found in 61 patients, and show a high frequency of CDI among both HCFO and CO groups. Our results of coinfection frequencies could support hypotheses that suggest Blastocystis can adapt to dysbiosis and oxidative stress. Further, the presence of toxigenic C. difficile occurring outside healthcare facilities shown here raises the alarm for community wide spread. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.